Pengetahuan dan Sikap Kepala Keluarga dalam Mematuhi Protokol Kesehatan di Masa Pandemi Covid-19 di RT Kelurahan Batu IX Tanjungpinang Timur - Samosir, Kholilah; Pitriyanti, Luh; Suci Daliana, Riski (Poltekkes Kemenkes Bengkulu, 2023)
Corona virus disease 2019 (COVID-19) has become a health problem that is in the spotlight and attention of the world. The number of COVID-19 cases in the Tanjungpinang City area in 2021 has reached 10,212 cases. Village Batu IX is the highest number of COVID-19 cases in Tanjungpinang City, namely 1,998 cases. This study aims to describe the knowledge and attitudes of the head of the family in complying with health protocols during the COVID-19 pandemic in RT Batu IX Village, Tanjungpinang Timur. This study uses quantitative descriptive research by means of interviews using questionnaires, sampling techniques using the purposive sampling with a total sample of 100 families residing in RT Batu IX Village. Data analysis using univariate. The results of this study indicate that the knowledge of the head of the family is good as many as 75 people (75.0%), sufficient knowledge of the head of the family as many as 20 people (20.0%) and lack of knowledge of the head of the family as many as 5 people (5.0%), and the good attitude of the head of the family as many as 25 people (25.0 %), enough attitude of the head of the family as many as 72 people (72.0%) and the attitude of less than the head of the family as many as 3 people (3.0%). The conclusions in this study were that the knowledge of the head of the family was good, while the attitude of the head of the family was sufficient in complying with the health protocol.